Global Nature, Global Brand: Bbc Earth and David Attenborough's Landmark Wildlife Series. Issue 1 (February 2013) - Richards, Morgan
Landmark wildlife series like Life on Earth (1979), Planet Earth (2006) and Frozen Planet (2011) are synonymous with the BBC, and are largely seen as unquestioned embodiments of its public service values. Yet the landmark format for wildlife programming was designed from its outset to appeal to international television markets, particularly the US market. This article examines the history and evolution of David Attenborough's landmark series, tracing the development of the landmark format from its roots in the BBC's programming policy of the early 1960s through broader changes in national and international television markets to the development of the global brand BBC Earth. Combining close analysis of landmark wildlife series with ethnographic interviews with BBC Natural History Unit staff and detailed archival research, the article focuses on the role of BBC wildlife documentary in debates about how public service media should be defined and understood. It is concluded that landmark wildlife series have always evinced the tensions between the BBC's public service values and the need for these series to appeal to global television markets.